Analysis of Product Defect to Reduce Return Product in Flexographic Printing - Apriyanti, Yunita; Zulkarnain (International Journal of Industrial Engineering and Engineering Management, 2023)
Product return in 2021 at PT XY increased, but the quality control implemented has not been running effectively. This study aims to analyze the failure risk that causes defects, gets the greatest failure risk in the Risk Priority Number (RPN),and gives suggestions for improvement for the next production. The focus of this study is on production defects that are returned by customers. This study used Failure Mode Effect Analysis (FMEA) methods and Problem Identification Corrective Action (PICA) table. From the gathered data, it is identified that there is one type of dominant defect that is outside the control limits. The results of data processing by multiplying the SOD value to get the RPN value found that the three largest ranking modes of failure were the engine settings did not match the RPN value of 484, negligent in the production control process with the RPN value is 230, and the compressor is not optimal with the RPN value is 210. Then an analysis was carried out using the PICA table to get suggestions for improvements, conducting periodic IK retraining, checking machine condition regularly, conducting periodic inspections during the production process, evaluating performance results, and running check sheets while carrying out the production process.